Disability Incidence Profile In Sukun Sub-District, Malang City - Rahmad, Rahmad (Journal of Innovation and Applied Technology, 2024)
Disability can be traced early with early detection/screening at primary health facilities, namely puskesmas, by involving the community. So far, the government has a Family/Community Based Rehabilitation (RBM) program aimed at mobilizing the community in providing assistance and support for persons with disabilities and their families by utilizing the potential of local social welfare sources. Disability can occur in all age groups, including children, adults and the elderly. The methods of this activity include: socialization to persons with disabilities. Disability screening, disability treatment as needed, and provision of assistive devices when needed according to the needs of patients with disabilities. This activity is expected to get great appreciation and interest from the target community, namely the elderly in the Malang City area. Follow-up of this activity is needed to ensure the sustainability of the disability treatment program in accordance with the Family / Community Based Rehabilitation Program.